Генетичні алгоритми для вирішення транспортних задач з використанням технологій штучного інтелекту - Ясько, О. С. (ХНУРЕ, 2024)
This work is focused on researching of artificial intelligence integration into the Traveling Salesman Problem (TSP) using Genetic algorithm. As time and precision are the key factors in the area as logistics, the work aims to provide an introduction to a method that can be applied in order to increase effectiveness of evolution algorithms for route planning. A method that only expands the possibilities for genetic operators such as selection, crossover, mutation and replacement which represent the real life evolution process
Keywords: вирішення транспортних задач; генетичний алгоритм